Advances in thermoelectrics. Issue 2 (3rd April 2018) - Mao, Jun; Liu, Zihang; Zhou, Jiawei; Zhu, Hangtian; Zhang, Qian; Chen, Gang; Ren, Zhifeng
Abstract : Thermoelectric generators, capable of directly converting heat into electricity, hold great promise for tackling the ever-increasing energy sustainability issue. The thermoelectric energy conversion efficiency is heavily dependent upon the materials' performance that is quantified by the dimensionless figure-of-merit ( ZT ). Therefore, the central issue in the research of thermoelectric materials lies in continuously boosting the ZT value. Although thermoelectric effects were discovered in the nineteenth century, it was only until the 1950s when classic materials like Bi2 Te3 and PbTe were developed and basic science of thermoelectrics was established. However, the research of thermoelectrics did not take a smooth path but a rather tortuous one with ups and downs. After hiatus in the 1970s and 1980s, relentless efforts starting from the 1990s were devoted to understanding the transport and coupling of electrons and phonons, identifying strategies for improving the thermoelectric performance of existing materials, and discovering new promising compounds. Rewardingly, substantial improvements in materials' performance have been achieved that broke the ZT limit of unity. Meanwhile, advancements in fundamental understanding related to thermoelectrics have also been made. In this Review, recent advances in the research of thermoelectric materials are overviewed. Herein, strategies for improving and decoupling the individual thermoelectric parameters are first reviewed, together with a discussion on open questions and distinctly different opinions. Recent advancements on a number of good thermoelectric materials are highlighted and several newly discovered promising compounds are discussed. Existing challenges in the research of thermoelectric materials are outlined and an outlook for the future thermoelectrics research is presented. The paper concludes with a discussion of topics in other fields but related to thermoelectricity.